2022
DOI: 10.1155/2022/7157444
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethyl Acetate Fraction from Eucommia ulmoides Leaves on PM2.5-Induced Inflammation and Cognitive Dysfunction

Abstract: This study aimed to evaluate the protective effect of the ethyl acetate from Eucommia ulmoides leaves (EFEL) on PM2.5-induced cognitive impairment in BALB/c mice. EFEL improved PM2.5-induced cognitive decline by improving spontaneous alternative behavioral and long-term memory ability. EFEL increased ferric reducing activity power (FRAP) in serum. In addition, EFEL increased superoxide dismutase (SOD) and reduced glutathione (GSH) contents and inhibited the production of malondialdehyde (MDA) in lung and brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Kong et al (2019) reported that the chlorogenic acid contained in E. ulmoides leaves improved MMP and ATP levels in paraquat-induced A549 cells [39]. According to Kim et al (2022), in PM 2.5 -induced mice, the ethyl acetate fraction of E. ulmoides leaves reduced ROS in mouse brain mitochondria and increased MMP and ATP levels [40]. These results demonstrate that AEEL can effectively ameliorate DSS-induced colitis mouse brain mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 89%
“…Kong et al (2019) reported that the chlorogenic acid contained in E. ulmoides leaves improved MMP and ATP levels in paraquat-induced A549 cells [39]. According to Kim et al (2022), in PM 2.5 -induced mice, the ethyl acetate fraction of E. ulmoides leaves reduced ROS in mouse brain mitochondria and increased MMP and ATP levels [40]. These results demonstrate that AEEL can effectively ameliorate DSS-induced colitis mouse brain mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 89%
“…causes an in ammatory response in the heart by interaction with TLRs and NF-κB signal [30]. Moreover, in previous studies, it was con rmed that PM 2.5 could produce various in ammatory factors [33][34][35].…”
Section: Protein Expression Of In Ammationmentioning
confidence: 92%
“…After the pellets and 1 × cell extraction buffer (10% SOD buffer, 0.4% ( v / v ) triton X-100, and 200 μM phenylmethan sulfonyl fluoride) were centrifuged at 4 °C for 10 min at 10,000× g . After processing, SOD contents were measured on absorbance 450 nm (Epoch 2) using the commercial SOD kit (Dojindo Molecular Technologies) [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
“…Inhaled PM 2.5 can easily pass through blood vessels and circulate throughout the whole body to reach several organs, causing apoptosis and inflammation with the activation of the toll-like receptor-4 (TLR-4)/myeloid differentiation primary response 88 (MyD88) pathway [ 4 ]. In addition, reactive oxygen species (ROS), oxidative stress, and mitochondrial dysfunction caused by exposure to fine dust cause various diseases in the human body [ 5 ]. Additionally, PM 2.5 reaches the gut through pulmonary mucus transport or direct intake; PM 2.5 that enters the gut can cause inflammation by increasing the expression of cytokines and changing the gut microbiome [ 6 ].…”
Section: Introductionmentioning
confidence: 99%